Reversible effects of vitamins C and E combination on oxidative stress-induced apoptosis in melamine-treated PC12 cells. (1st February 2014) - An, L.; Li, Z.; Zhang, T.
Abstract: Due to its high nitrogen content, melamine was deliberately added to raw milk for increasing the apparent protein content. Previous studies showed that melamine-induced apoptosis and oxidative damage on PC12 cells and rats' hippocampus. Several evidences suggested that vitamin antioxidant reduced oxidative stress and improved organic function. Whether treatments with antioxidant vitamins C or E, otherwise combination of them can attenuate oxidative stress after melamine administration remains to be elucidated. In this study, the reversible effects of vitamin antioxidants was investigated on melamine-induced neurotoxicity in cultured PC12 cells, an in vitro model of neuronal cells. When comparing vitamin C and E, the combination of both statistically increased PC12 cells viability. The results further showed that vitamin complex has effectively reduced the formation of reaction oxygen species, decreased the level of malondialdehyde, and elevated the activities of antioxidative enzymes. Hoechst 33342 staining and flow cytometric analysis of apoptosis showed that vitamin combination treatment effectively prevented PC12 cells from this melamine-induced apoptosis. It revealed the apoptotic nuclear features of the melamine-induced cell death. Additionally, a combination treatment of vitamins effectively inhibited apoptosis via blocking the increased activation of caspase-3. In summary, the vitamin E and C combination treatment could rescue PC12 cells from the injury induced by melamine through the downregulation of oxidative stress and prevention of melamine-induced apoptosis.